Contraband Cultures (UCL Press, 2024)
Contraband Cultures presents narratives, representations, practices and imaginaries of smuggling and extra-legal or informal circulation practices, across and between the Latin American region (including the Caribbean) and its diasporas. Countering a fetishizing and hegemonic imaginary (typically stemming from the Global North) of smuggling activity in Latin America as chaotic, lawless, violent and somehow ‘exotic’, this book reframes such activities through the lenses of kinship, political movements, economic exchange and resistance to capitalist state hegemony.